2011
DOI: 10.1017/s0007114511004880
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Nutritional Assessment predicts functional decline of elderly Taiwanese: result of a population-representative sample

Abstract: Nutrition is a key element in geriatric health and is important for functional ability. The present study examined the functional statuspredictive ability of the Mini-Nutritional Assessment (MNA). We analysed the dataset of the 'Survey of Health and Living Status of the Elderly in Taiwan', a population-based study conducted by the Bureau of Health Promotion of Taiwan. Study subjects ($ 65 years old) who completed both the 1999 and 2003 surveys were rated with the long form and short form of the MNA at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 28 publications
4
21
0
Order By: Relevance
“…However, MNA was significantly correlated with the SPPB total score, demonstrating a possible influence of nutritional status on the functionality of the elderly. This finding agrees with the results of Lee et al 36 , who demonstrated an association between of ADL measures and MNA. Bahat et al 37 , however, found no association between MNA and functionality but did find a correlation between functionality and lean mass as assessed by electrical bioimpedance.…”
Section: Discussionsupporting
confidence: 93%
“…However, MNA was significantly correlated with the SPPB total score, demonstrating a possible influence of nutritional status on the functionality of the elderly. This finding agrees with the results of Lee et al 36 , who demonstrated an association between of ADL measures and MNA. Bahat et al 37 , however, found no association between MNA and functionality but did find a correlation between functionality and lean mass as assessed by electrical bioimpedance.…”
Section: Discussionsupporting
confidence: 93%
“…This prevalence was 10 times as high as that in nondisabled elderly [27]. Similarly, 22.5% of the subjects in our study were underweight, with BMI values <18.5 kg/m 2 .…”
Section: Discussionsupporting
confidence: 65%
“…The total KCL score closely correlated with physical function (walking time), nutrition (MNA) and depressive mood (GDS‐15). These categories are reportedly related to future dependence, and are included in many frailty screens . Sewo Sampaio et al .…”
Section: Discussionmentioning
confidence: 99%